Combating food insecurity and creating sustenance: addressing the root causes of hunger in the US through political empowerment and public policy engagement. Issue 2 (1st February 2023) - Pine, Adam
ABSTRACT: This commentary advocates for food assistance programmes that support political empowerment and public policy participation among those experiencing food insecurity. This change will help transform hunger programmes from stigmatising support programmes into vehicles to end hunger. Food insecurity is not an isolated phenomenon, but a symptom of historical socio-political marginality such as settler colonialism, Jim Crow segregation, racial gerrymandering, anti-immigrant policies and neoliberal cutbacks to worker's wages and union organising rights. In sum, people are hungry because they are cut out of power, and for working people to be fed feeding lines must be transformed into spaces of empowerment and public policy voice.